2018
DOI: 10.1016/j.amjcard.2018.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Testosterone Levels to Mortality in Men With Heart Failure

Abstract: We aimed to investigate the impact of testosterone on the prognosis of heart failure (HF), as well as the underlying cardiac function, cardiac damage, and exercise capacity. We analyzed consecutive 618 men with HF (age 65.9 years). These patients were divided into quartiles based on their serum levels of total testosterone (TT): first (TT > 631 ng/dl, n = 154), second (462 < TT ≤ 631 ng/dl, n = 155), third (300 < TT ≤ 462 ng/dl, n = 156), and fourth (TT ≤ 300 ng/dl, n = 153) quartiles. In the Kaplan-Meier anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
0
19
1
2
Order By: Relevance
“…As described previously, 18,19 we diagnosed several comorbidities, which often coexist and are associated with adverse prognosis in patients with HF. CKD was defined as an estimated glomerular filtration rate <60 mL/min/1.73 cm 2 according to the Modification of Diet based on Renal Disease formula.…”
Section: Discussionmentioning
confidence: 90%
“…As described previously, 18,19 we diagnosed several comorbidities, which often coexist and are associated with adverse prognosis in patients with HF. CKD was defined as an estimated glomerular filtration rate <60 mL/min/1.73 cm 2 according to the Modification of Diet based on Renal Disease formula.…”
Section: Discussionmentioning
confidence: 90%
“…34 Another contributing factor to sarcopenia is a variable degree of malnutrition 56 that may be caused by inflammatory cytokines, 57-59 which have been known to contribute to anorexia in chronic disease. 68 However, testosterone deprivation therapy due to prostate cancer selectively impairs lower-limb muscle function, primarily affecting muscles that support body weight, mediate the forward movement the body during walking, and mediate balance. 64 Malnutrition and sarcopenia have also been shown to be associated with early post-liver transplant morbidity/mortality, yet allocation indices do not include nutritional status.…”
Section: Chronic Heart Failure and Muscle Maintenancementioning
confidence: 99%
“…67 A recent study has identified low testosterone in men as an independent risk factor in CHF. 68 However, testosterone deprivation therapy due to prostate cancer selectively impairs lower-limb muscle function, primarily affecting muscles that support body weight, mediate the forward movement the body during walking, and mediate balance. 69 On the other hand, supplementation of androgens such as dihydrotestosterone in mice reversed the reduction in protein synthesis and amino acid transporter expression observed in ageing animals.…”
Section: Chronic Heart Failure and Muscle Maintenancementioning
confidence: 99%
“…The definition of target comorbidities (ie, hypertension, diabetes, dyslipidemia, chronic kidney disease, and anemia) was mentioned in a previous work . The definition of hypertension was the recent use of antihypertensive medications, a systolic blood pressure of ≥140 mm Hg, and/or a diastolic blood pressure of >90 mm Hg.…”
Section: Methodsmentioning
confidence: 99%